“Da brincadeira a resistência”: defendendo a territorialidade através da festa do coco de roda no Quilombo do Ipiranga, município do Conde / PB - Barbosa, Katiusca Lamara dos Santos (2022)
This thesis explores the cultural practice of coco de roda in the quilombola community of Ipiranga, located on the southern coast of the state of Paraíba, in the city of Conde. The coco de roda is a traditional community activity in the region; however, because of territorial disputes and struggles, the coco de roda was used as a tool of resistance and cultural affirmation. When these conflicts ended in the late 1980s, the group Novo Quilombo was formed, through the initiative of Master Lenita and her daughter Master Ana. Both residents of Ipiranga were involved with the struggles of the workers in the region for the right to own the land where they work and live. The coco de roda was present in these struggles as well as in the family context. In order to perform on a regular basis in Ipiranga, mother and daughter created the coco party. They perceived in this practice the way for mediation to carry out the process of conscientization, awareness, expression, and affirmation of the community and its players, struggles and social roles. Within this context, this work presents, analyzes, and reflects, from the context of the cultural practice of coco de roda at the Ipiranga community party the concept of construction on the defense of the territory and territoriality of the quilombola community of Ipiranga from the musical context of the coco party. The methodological basis of this work consists of ethnographic research between 2018 and 2021, with participant observation, interviews and audiovisual records. Based on bibliographical research developed in this same period, the epistemological and theoretical dimensions are structured in studies that refer to the party phenomenon, participatory performance sociocolaborative network, territory and territoriality, articulating areas such as ethnomusicology, anthropology and sociology. In this way, the results show that the practice of coco de roda, in the socio-interactive scope of music-making during the party is important for the process of (re)production of the party phenomenon, and the mechanism or tool used is the collaborative interaction through participatory performance. This interpretation leads to the substantiation of the thesis that the music of coco de roda belongs to a larger and more complex activity in which the party-performance is a mediator in the notion of construction, defense and maintenance of the territory and territoriality of the community of Ipiranga. More specifically, I argue that the organization of the cultural practice of coco de roda in the community of Ipiranga is accomplished through a process of collaborative social interactions mediated by the intersection of music, song, and dance in the space-time of the performance-party.